1973
DOI: 10.1111/j.1432-1033.1973.tb03048.x
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Arginine Kinase from Drosophila melanogaster

Abstract: 1. Starch‐gel electrophoresis of extracts of several strains of the genus Drosophila reveals neither allelic variants nor isoenzymes of arginine kinase. Arginine kinase of the drosophilid Zaprionus vittiger migrates differently. 2. Arginine kinase is non‐uniformly distributed in tissues of Drosophila melanogaster. The activity in muscle tissue represents about 70% of the total activity. A characteristic fluctuation of the enzyme activity during the development from the egg to the adult stage can be observed. 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

1975
1975
2011
2011

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 18 publications
2
17
0
Order By: Relevance
“…Results of initial velocity studies of the forward reaction at low substrate concentrations suggest that the reaction mechanism is of a sequential type. These data are similar to those found for APK in other insects (Cheung, 1973;Wallimann & Eppenberger, 1973).…”
Section: -supporting
confidence: 90%
See 1 more Smart Citation
“…Results of initial velocity studies of the forward reaction at low substrate concentrations suggest that the reaction mechanism is of a sequential type. These data are similar to those found for APK in other insects (Cheung, 1973;Wallimann & Eppenberger, 1973).…”
Section: -supporting
confidence: 90%
“…The relatively high activity found in freshly laid eggs in comparison with other developmental stages is unexpected. Low levels of APK activity were reported in eggs from Drosophila melanogaster by Wallimann and Eppenberger (1973).…”
Section: Discussionmentioning
confidence: 99%
“…On a global scale, this could help with problems of world hunger and the prevention of over-fishing of oceans for fish-meal production. Interestingly Cr supplementation of Drosophila melanogaster , known to express arginine kinase (AK) instead of CK (Wallimann and Eppenberger 1973), protects these flies from oxidative stress caused by exposure to rotenone, a potent mitochondrial toxin, and paraquat, a potent herbicidal redox cycler, that both generate ROS (Hosamani et al 2010). Since these insects are not able to phosphorylate Cr into PCr, the protective effects of Cr observed cannot be due to improved cellular energetics, but are more likely related to anti-oxidant and/or anti-apoptotic effects of this guanidino compound.…”
Section: Creatine—nutritional Constituent and Supplementationmentioning
confidence: 99%
“…In arthropods, phospho-L-arginine appears to serve as the predominant phosphagen, that is a substrate of the corresponding arginine kinases (Lohmann, 1935;Lewis and Fowler, 1962;Virden et al, 1965;Blethen, 1972;Strong and Ellington, 1995). Arginine kinase has been studied in a number of insect groups, including muscid flies (Lewis and Fowler, 1962;Sacktor and Hurlbut, 1966;Rockstein and Kumar 1972;Wallimann and Eppenberger, 1973;Wyss et al, 1995), locusts (Newsholme et al, 1978;Schneider et al, 1989;Li et al, 2006), lepidopterans (Rosenthal et al, 1977;Chamberlin, 1997;Binder et al, 2001), hymenopterans (Kucharski and Maleszka, 1998;Wang et al, 2009), cockroaches and beetles (Tanaka et al, 2007). The majority of the studies concluded the presence of a single type of enzyme with approximately 40 000 Da molecular mass, that is presumably encoded by a single copy gene.…”
Section: Introductionmentioning
confidence: 98%